2009
DOI: 10.1088/0963-0252/18/3/035018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma breakdown diagnostics with the biased disc of electron cyclotron resonance ion source

Abstract: The electron cyclotron resonance ion sources at the JYFL (University of Jyväskylä, Department of Physics) accelerator laboratory have been operated in pulsed mode to study the time-resolved current signal from the biased discs of the ion sources. The purpose of the experiments is to gain an understanding of the ion source parameters affecting the time required for the transition from neutral gas to plasma. It was observed that the plasma breakdown time depends strongly on the neutral gas density, gas species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…The transistorNote: Contributed paper, published as part of the Proceedings of the 16th International Conference on Ion Sources, New York, New York, USA, August 2015. a) olli.tarvainen@jyu.fi transistor logic (TTL) signal driving the switch was used as a trigger for the data acquisition consisting of current measurement from the biased disc across 1 kΩ resistor, a Bismuth germanate (BGO) scintillator coupled with a Nadoped CsI photomultiplier tube (PMT) and m/q-resolved measurement of the extracted beam currents with a Faraday cup. The bias disc current was recorded in order to determine the delay 5 between the leading edge of the microwave pulse and the plasma breakdown. The scintillator was used for detecting periodic bursts 1 of wall bremsstrahlung generated by energetic electrons expelled from the magnetic confinement as a result of the kinetic instabilities.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The transistorNote: Contributed paper, published as part of the Proceedings of the 16th International Conference on Ion Sources, New York, New York, USA, August 2015. a) olli.tarvainen@jyu.fi transistor logic (TTL) signal driving the switch was used as a trigger for the data acquisition consisting of current measurement from the biased disc across 1 kΩ resistor, a Bismuth germanate (BGO) scintillator coupled with a Nadoped CsI photomultiplier tube (PMT) and m/q-resolved measurement of the extracted beam currents with a Faraday cup. The bias disc current was recorded in order to determine the delay 5 between the leading edge of the microwave pulse and the plasma breakdown. The scintillator was used for detecting periodic bursts 1 of wall bremsstrahlung generated by energetic electrons expelled from the magnetic confinement as a result of the kinetic instabilities.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The resulting minimum-B topology provides a closed ECR surface for efficient resonant energy transfer from microwaves to the plasma electrons, enables sufficient plasma confinement for the step-wise ionization of high charge states, and suppresses magneto-hydrodynamic instabilities. 8 The electron energy distribution resulting from the resonant heating and long confinement time of energetic electrons 9 is strongly anisotropic and is considered to consist of (at least) two main populations: cold (and warm) electrons with an average energy of E e,cold ¼ 10 eV-10 keV and hot electrons with E e,hot > 10 keV up to 1 MeV. 10,11 Such non-equilibrium plasmas are prone to kinetic instabilities driven by warm and hot electrons whose transverse (with respect to the external magnetic field) velocity V ?…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on this subject has been conducted with time resolved electrical probes, emission spectroscopy and bremsstrahlung radiation diagnostics under a wide range of parameters for different plasmas [3][4][5]. Understanding the plasma processes involved during the breakdown is beneficial for monocharged beam current optimization as well as the improvement of multiple charged ion production efficiency [6][7][8]. On the other hand, the value of ultrafast light intensified photography in plasma dynamics research has been demonstrated by decades of experimentation in high density plasmas as Z-pinches, Exploding Wires and Plasma Foci [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%